Consumo de presas por Argiope argentata (F.) (Araneae: Araneidae) y Plesiometa argyra (Walkenaer) (Araneae: Tetragnathidae) en arroz irrigado en Colombia - Bastidas López, Harold; Pantoja López, Alberto; Hernández M., María del Pilar (1994)
The feeding habits of two spider species, Plesiometa argyra (Walkenger) and A. argentata (F), was studied during 1992 on irrigated rice fields of Colombia. The number of carcasses/web was similar for both species, but a significantly higher number of arthropods/carcass was recorded for P. argyra. Eighty three percent of the arthropods collected for this species belong to Diptera (35.5 percent) and Homoptera (48.2 percent).